COVID-19 - postinfectious hypercoagulable state as a probable cause of basilar artery occlusion - Case Report - Kędra, Kamila; Michalik, Izabela; Bielak, Maciej; Wiącek, Marcin (Journal of Education, Health and Sport, 2023)
Covid-19 can manifest with serious neurological complications and hypercoagulability. Latest data from China showed neurological complications in 36% of 214 COVID-19 patients- mainly ischemic stroke. Coagulopathy associated with Covid-19 was reported to increase the risk of stroke also in young adults without comorbidities. A 29-year-old patient with hypertension admitted to the hospital with dysarthric speech and balance disorders and dizziness with vomiting was referred for thrombectomy of an occluded basilar artery after ineffective RTPA therapy. After the thrombectomy, a gradual reduction in the neurological deficit was observed-the permeability of the basilar artery was restored. However, during the intervention, the posterior right cerebral artery was damaged and a short-term extravasation of the contrast blood to the subarachnoid space occurred. MRI showed minor multifocal ischemic changes in the area of the cerebellum, pons and cerebral peduncle. In the pre-hospital interview a week earlier, transient changes in smell and taste were noted. On the day of admission, the patient had a negative antigen and PCR tests for SARS-CoV-2- virus. Laboratory tests showed high D-Dimers (5696 H ng /ml) and reduced fibrinogen. After mechanical thrombectomy, the patient reported double vision when looking straight and left. He was correctly oriented with slight ataxia and a deficit of strength in the left limbs, meningeal symptoms were negative. It is important to understand the association between Covid 19 and the possibility of an ischemic stroke and coagulation changes in order to choose appropriate stroke treatment methods.